Next generation sequencing unravels the biosynthetic ability of Spearmint (Mentha spicata) peltate glandular trichomes through comparative transcriptomics - Jin, Jingjing (BMC Plant Biol, 2014)
BACKGROUND: Plant glandular trichomes are chemical factories with specialized metabolic capabilities to produce diverse compounds. Aromatic mint plants produce valuable essential oil in specialised glandular trichomes known as peltate glandular trichomes (PGT). Here, we performed next generation transcriptome sequencing of different tissues of Mentha spicata (spearmint) to identify differentially expressed transcripts specific to PGT. Our results provide a comprehensive overview of PGT’s dynamic metabolic activities which will help towards pathway engineering. RESULTS: Spearmint RNAs from 3 different tissues: PGT, leaf and leaf stripped of PGTs (leaf-PGT) were sequenced by Illumina paired end sequencing. The sequences were assembled de novo into 40,587 non-redundant unigenes; spanning a total of 101 Mb. Functions could be assigned to 27,025 (67%) unigenes and among these 3,919 unigenes were differentially expressed in PGT relative to leaf - PGT. Lack of photosynthetic transcripts in PGT transcriptome indicated the high levels of purity of isolated PGT, as mint PGT are non-photosynthetic. A significant number of these unigenes remained unannotated or encoded hypothetical proteins. We found 16 terpene synthases (TPS), 18 cytochrome P450s, 5 lipid transfer proteins and several transcription factors that were preferentially expressed in PGT. Among the 16 TPSs, two were characterized biochemically and found to be sesquiterpene synthases. CONCLUSIONS: The extensive transcriptome data set renders a complete description of genes differentially expressed in spearmint PGT. This will facilitate the metabolic engineering of mint terpene pathway to increase yield and also enable the development of strategies for sustainable production of novel or altered valuable compounds in mint. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-014-0292-5) contains supplementary material, which is available to authorized users.